Enforcement and Compliance: The Case of Mandated CSR Provisions in an Emerging Economy. (February 2023) - Arora, Akshita
This study is an insight into Securities Exchange Board of India's (SEBI) mandatory corporate social responsibility (CSR) provisions for corporates and the status of their implementation in an emerging economy. We have analysed a sample of listed Indian companies with regard to expenditure on CSR activities, that is, whether they meet the legislative requirements for CSR spend. The study examines relevant data from 2015 to 2020 post the introduction of the mandatory 2% CSR bill. We have assessed the implementation status of mandatory CSR reforms introduced by The Companies Act, 2013 and followed up in the amendment bills. The results show that there is a substantial increase in the expenditure on CSR after acquiring the mandatory status. Although all sample companies have made disclosures on CSR norms, some companies have not fulfilled the mandatory CSR expenditure norms under Section 135. Corporate entities are cognisant of the legislation on CSR and the level of compliance is exemplary. The mandated CSR policy in India has shown remarkable results in terms of CSR spend but to set further norms in this area, it should be analysed whether this ideology of incurring expenses on socially responsible activities has any adverse corollaries. In this study, we have discussed the practical implications of the regulatory amendments in CSR provisions on the Indian corporate sector.